ANALISIS KUALITAS BATANG PISTON ORIGINAL DAN NON ORIGINAL PADA KENDARAAN RODA DUA 4 LANGKAH KAPASITAS 113 CC - Kis Yoga Utomo; Ahmad Zayadi; Masyhudi; Deni A (Universitas Krisnadwipayana, 2022)
Quality Analysis of Original and Non-Original Piston Rods on Two-Wheel Vehicles 4 Stroke Capacity 113cc, piston rods are important spare parts on motorcycles, because their function is to transmit the powergenerated in the combustion process from the piston to the crankshaft on the vehicle. If there is damage tothe piston rod which can cause the piston rod to be bent or even broken, so that it has an impact on thesafety factor when driving a motor vehicle. The purpose of this study was to determine the mechanicalcharacteristics of the piston rod material (connecting rod) of original and non-original products, and tocompare the quality of the piston rods of original and non-original products from two differentmanufacturers. The method used in this study was the ASTM E 3 microstructure test, the SNI 19-0409-1989hardness test, and the ASTM A 751 chemical composition. Metallographic testing revealed that themicrostructure of the original motorcycle piston rod was tempered martensite with a fine grain of 60-80 cm.70%, while the microstructure of the non-original motorcycle piston rod is tempered martensite with 40%coarse grain. Medium hardness test The hardness value of the original piston rod material is 428 HV, whichis higher than the non-original motorcycle piston rod material hardness value of 396 HV. As well as testingthe chemical composition that the value of the element Al contained in the original motorcycle piston rodmaterial is 0.0314% > 0.0184% non-original motorcycle piston rod material in the chemical compositiontesting process.